2013
DOI: 10.4103/1319-2442.106364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of renal disease in Nigerian children infected with the human immunodeficiency virus and on highly active anti-retroviral therapy

Abstract: Access to highly active anti-retroviral therapy (HAART) has improved the prognosis of Nigerian children infected with the human immunodeficiency virus (HIV); thus, more children are surviving. Long-term exposure to HAART is potentially nephrotoxic. We therefore aimed at assessing the prevalence of renal disease in Nigerian children infected with HIV, who are on HAART. In this cross-sectional study, we studied children, aged ten months to 17 years, infected with HIV, attending the pediatric HIV clinics of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 16 publications
6
36
2
Order By: Relevance
“…In Sub-Saharan Africa, there are a few studies which describe the extent of renal disease in HIV-infected children. In Nigeria, Iduoriyekemwen et al found the prevalence of renal disease in HIV-infected children on highly active antiretroviral therapy (HAART) to be 16.2% [8]. Some of the studies in sub-Saharan Africa focused on proteinuria since it has been shown to be an early marker for HIVAN.…”
Section: Introductionmentioning
confidence: 99%
“…In Sub-Saharan Africa, there are a few studies which describe the extent of renal disease in HIV-infected children. In Nigeria, Iduoriyekemwen et al found the prevalence of renal disease in HIV-infected children on highly active antiretroviral therapy (HAART) to be 16.2% [8]. Some of the studies in sub-Saharan Africa focused on proteinuria since it has been shown to be an early marker for HIVAN.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study only evaluated a single measurement of microalbuminuria. 19 Low prevalence in our study was associated with lower risk factors observed in subjects, for example, younger age, 3,11 non-advanced clinical staging, 9,31 high CD4 cell count, 9,11,18 and already having received antiretroviral therapy at the time of study. 7,17 We found no relationships between persistent proteinuria and age, clinical stage, immunological classification, or duration of ARV.…”
Section: Discussionmentioning
confidence: 80%
“…In subjects with abnormalities of the kidney, 87.5% had been taking ARV < 5 years. 19 The use of antiretroviral drugs affected the low prevalence of proteinuria in this study because all subjects included in the final evaluation had been on ARV. ARV therapy restores renal epithelial changes characterized by a significant decrease in albuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations